Perkembangan Kemandirian Keuangan Daerah Kabupaten/Kota Di Provinsi Papua Barat - Albertus Girik Allo (Pusat Penelitian Pemberdayaan Fiskal dan Ekonomi Daerah (P3FED) Universitas Papua, 2021)
Law Number 22 of 1999 on Local Government has changed the system of government in Indonesia to become decentralized, including those related to finance. The purpose of this study is to see the trend of financial independence in the districts/cities in West Papua Province. The measure used to assess this is the ratio of regional financial effectiveness and the degree of fiscal independence. The data used is sourced from the Directorate General of Fiscal Balance, Ministry of Finance of the Republic of Indonesia period 2010 – 2019. The results of the analysis show that the financial effectiveness ratio of districts/cities in West Papua Province has been very effective. However, the degree of fiscal independence shows the opposite condition, where all districts/cities in West Papua Province are still in “belum mandiri” category.